Media Portrayals of People with Disabilities: An Analysis of Malaysia’s Television Series,“Kerana Cintaku Saerah” (Because of My Love, Saerah) - Aina Razlin, Mohammad Roose; Ross Azura, Zahit; Sheilla Lim, Omar Lim (UNIMAS Publisher, 2016)
The media has a powerful ability to influence and shape society’s perceptions towards people with disabilities. The portrayal of individuals with disabilities within the me-dia can often have an enormous impact on the way that are perceived by viewers. In Malaysia, people with disabilities are frequently viewed as pitiful, thus medias are more likely to use the element of sympathy in order to garner support from its target-ed audience. The focus of this article is on the portrayal of people with disabilities in a popular television series in Malaysia, Kerana Cintaku Saerah (Because of My Love, Saerah) through the analysis of; self-acceptance by the characters with disabilities, family and society’s acceptance, and disability stereotypes in the Malay society. The findings revealed the ideation of how people with disabilities are treated, as well as exhibits disability stereotypes that exist in the Malay society.